Development of a Modified Punch Test for Investigating the Failure Behavior in Sheet Metal Materials - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)

Experimental and numerical investigation of the influence of multiaxial loading conditions on the failure behavior of clinched joints - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering)
Since the application of mechanical joining methods, such as clinching or riveting, offers a robust solution for the generation of advanced multi-material connections, the use in the field of lightweight designs (e.g. automotive industry) is steadily increasing. Therefore, not only the design of an individual joint is required but also the dimensioning of the entire joining connection is crucial. However, in comparison to thermal joining techniques, such as spot welding, the evaluation of the joints’ resistance against defined requirements (e.g. types of load, minimal amount of load cycles) mainly relies on the consideration of expert knowledge, a few design principles and a small amount of experimental data. Since this generally implies the involvement of several domains, such as the material characterization or the part design, a tremendous amount of data and knowledge is separately generated for a certain dimensioning process. Nevertheless, the lack of formalization and standardization in representing the gained knowledge leads to a difficult and inconsistent reuse, sharing or searching of already existing information. Thus, this contribution presents a specific ontology for the provision of cross-domain knowledge about mechanical joining processes and highlights two potential use cases of this ontology in the design of clinched and pin joints.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)
The application of the mechanical joining process clinching enables the joining of sheet metals with a wide range of material-thickness configurations, which is of interest in lightweight construction of multi-material structures. Each material-thickness combination results in a joint with its own property profile that is affected differently by variations. Manufacturing process-related effects from preforming steps influence the geometric shape of a clinched joint as well as its load-bearing capacity. During the clinching process high degrees of plastic strain, increased temperatures and high strain rates occur. In this context, a 3D numerical model was developed which can represent the material-specific behaviour during the process chain steps sheet metal forming, joining, and loading phase in order to achieve a high predictive accuracy of the simulation. Besides to the investigation of the prediction accuracy, the extent of the influence of individual modelling aspects such as temperature and strain rate dependency is examined.

Numerical investigation of a friction test to determine the friction coefficients for the clinching process - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.
Keywords: Mechanical Engineering; General Materials Science

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, Lars; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, Martina (Production Engineering)
In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

A Review on the Modeling of the Clinching Process Chain - Part I: Design Phase - Schramm, Britta; Martin, Sven; Steinfelder, Christian; Bielak, Christian Roman; Brosius, Alexander; Meschut, Gerson; Tröster, Thomas; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

A Review on the Modeling of the Clinching Process Chain - Part II: Joining Process - Schramm, Britta; Friedlein, Johannes; Gröger, Benjamin; Bielak, Christian Roman; Bobbert, Mathias; Gude, Maik; Meschut, Gerson; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Further development of a numerical method for analyzing the load capacity of clinched joints in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

Concept development of a method for identifying friction coefficients for the numerical simulation of clinching processes - Böhnke, Max; Rossel, Moritz Sebastian; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The International Journal of Advanced Manufacturing Technology)
Abstract In order to reduce fuel consumption and thus pollutant emissions, the automotive industry is increasingly developing lightweight construction concepts that are accompanied by an increasing usage of aluminum materials. Due to poor weldability of aluminum in combination with other materials, mechanical joining methods such as clinching were developed and established in series production. In order to predict the relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard, the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals as well as between the sheet metal and clinching tools has a significant impact on the geometrical formation of the clinched joint. No testing methods exist that can sufficiently investigate the frictional behavior in sheet materials, especially under high interface pressures, different relative velocities, and long friction paths, while allowing a decoupled consideration of the test parameters. This paper describes the development of further testing concepts based on a proven tribo-torsion test method for determining friction coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum and steel sheet material in clinching processes is investigated using numerical simulation. Based on these findings, the developed concepts focus on determining friction coefficients at interface pressures of the above materials, yield stress, as well as the reproduction of the occurring friction conditions between sheet metal materials and tool surfaces in clinching processes using tool substitutes. Furthermore, wear investigations between sheet metal material and tool surface were carried out in the friction tests with subsequent EDX analyses of the frictioned tool surfaces. The developed method also allows an optical deformation measurement of the sheet metal material specimen by means of digital image correlation (DIC). Based on a methodological approach, the test setups and the test systems used are explained, and the functionality of the concepts is proven by experimental tests using different sheet metal materials.

Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of rivet length on joint formation on self-piercing riveting process considering further process parameters - Kappe, Fabian; Bielak, Christian Roman; Sartisson, Vadim; Bobbert, Mathias; Meschut, Gerson (ESAFORM 2021)
Driven by the CO2-emission law by the European government and the increasing costs for raw materials as well as energy, the automotive industry is increasingly using multi-material constructions. This leads to a continuous increase in the use of mechanical joining techniques and especially the self-piercing riveting is of particular importance. The reason for this is the wide range of joining possibilities as well as the high load-bearing capacities of the joints. To be able to react to changing boundary conditions, like material thickness or strength variation of the sheets, research work is crucial with regard to the increase of versatility. In this paper, a numerical study of the influences on the selfpiercing riveting process is presented. For this purpose, the influence of different process parameters such as rivet length and die depth on various quality-relevant characteristics were investigated. With the help of the design of experiment, significant influences were determined and interactions between the individual parameters are shown.

Influence of various procedures for the determination of flow curves on the predictive accuracy of numerical simulations for mechanical joining processes - Böhnke, Max; Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Materials Testing)
The predictive quality of numerical simulations for mechanical joining processes depends on the implemented material model, especially regarding the plasticity of the joining parts. Therefore, experimental material characterization processes are conducted to determine the material properties of sheet metal and generate flow curves. In this regard, there are a number of procedures which are accompanied by varying experimental efforts. This paper presents various methods of determining flow curves for HCT590X as well as EN AW-6014, including varying specimen geometries and diverse hardening laws for extrapolation procedures. The flow curves thus generated are compared considering the variety of plastic strains occurring in mechanical joining processes. The material data generated are implemented in simulation models for the joining technologies, clinching and self-piercing riveting. The influence of the varied methods on the predictive accuracy of the simulation model is analysed. The evaluation of the differing flow curves is achieved by comparing the geometric formation of the joints and the required joining forces of the processes with experimentally investigated joints.

Numerical analysis of the robustness of clinching process considering the pre-forming of the parts - Bielak, Christian Roman; Böhnke, Max; Beck, Robert; Bobbert, Mathias; Meschut, Gerson (Journal of Advanced Joining Processes.)
Keywords: Clinching; process simulation; FEM; pre-straining; sensitivity analysis

Development of a numerical method for analyzing the robustness of clinching in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson